Uji Filtrasi Heat and Moisture Exchangers (HME) dalam Menyaring Gas Formaldehida - Jumanto Jumanto; Supangat Supangat; Al Munawir (Journal of Telenursing (JOTING), 2022)
This study aims to examine the use of Heat and Moisture Exchangers (HME) filters in filtering volatile organic compounds (formaldehyde) produced from surgical fumes, a side effect of using hazardous electrical-based surgical instruments. The method used is the descriptive method with a total sample of 15, divided into three groups, namely HME1, HME2 and HME3. The results showed that the HME1 filter obtained the highest formaldehyde value of 15.95 ppm and the lowest of 10 ppm with a mean value of 12.99 ppm; HME2 filter with the highest formaldehyde value of 13.98 ppm, the lowest 7.98 ppm and the mean value of 9.58 ppm; the HME3 filter showed the highest formaldehyde value of 11.98 ppm and the lowest of 4.99 ppm with a mean number of 4.99 ppm. In conclusion, there is a difference in the average amount of smoke after being given the action of the filter modification method (HME1, HME2 and HME3). The modified filter can be used to capture/filter surgical fumes. Keywords: Surgical Fumes, Electrosurgical Unit, HME Filter, Formaldehyde, Breast Cancer